Upaya Peningkatan Dosen Sebagai Reviewer Melalui Pelatihan Reviewer Jurnal - Fadhilah, Umu; Sina, Cian Ibnu; Pujiati, Wasis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Scientific publications measure the progress of scientific education in a region or agency. A good publication must fulfill good writing rules and standards.  A reviewer plays an important role in this journal publication process. This Community service was to improve the competence of lecturers as journal reviewers at the Stikes HangTuah Tanjungpinang institution.  This training was held for one day on 12 June 2024. The training was carried out offline. At the Stikes HangTuah Meeting Room Jl. W.R. Supratman, Air Raja, Kec. Tanjungpinang Tim., Tanjung Pinang City, Riau Islands. Participants who participated in the training were all permanent lecturers of Stikes HangTuah The training was held for one day. The steps taken in this training, 1) Giving a Pre-test to participants to find out the participants' knowledge about OJS and reviewing manuscripts and providing training materials (2 Providing material through lectures, discussions, and offline practices (3 Evaluation after conducting training by giving several questions related to the ability of participants after being given training material through google form media. The post-test results showed an increase of 100% for knowledge questions about the participant's knowledge of the Open Journal System (OJS) website. This proves that OJS is not a new thing for training participants while as much as 100%. Survey results have known how to publish journals This proves that OJS is not a new thing for training participants, while 100%. The survey results know how to publish their journals through the OJS platform. The participant's experience as article reviewers before training was 74%, and 44% had become reviewers, this proves that the lecturers already had experience as reviewers before training but there has not been a significant increase in knowledge. After the training, there was an increase of 100% in the ability of participants to review articles through OJS directly. This shows that the participants managed to understand the entire material presented by the speaker, and this PkM activity was successful with an average survey result of 100%. So it can be concluded that the material provided during the training was useful and improved the ability of lecturers as reviewers by the needs of journal development that they manage.